Training university teachers in an urban context to educate future teachers in rural Mayan environments: an international cooperation project - Fernández-Larragueta, Susana; Martínez-Martínez, María José; Muñoz-López, Johana (Frontiers in Education, 2023)
This article is part of an International Cooperation Project funded by the Andalusian Agency for Development Cooperation of the Junta de Andalucía, Spain in collaboration with the Mayan Technological Institute (ITMES) in San Juan de Chamelco-Cobán at the University of San Carlos de Guatemala: 2018UC006 “Maestras y maestros para niñas y niños mayas en zonas rurales diseminadas: formando los formadores.” (Teachers for Mayan girls and boys in remote rural areas: training the trainers). This cooperation project arose from the need of the university unit attached to the University of San Carlos to develop a university degree program in teacher training in bilingual infant and primary education that would consider the characteristics of the communities these new professionals would impact rural Mayan communities. In this sense, ITMES is particularly interesting for three reasons: (1) the unit is attached to the University of San Carlos, the only public university in Guatemala, as a response to the Guatemalan Constitution that indicates the need for a Mayan University; (2) the unit’s distinctive development for the formation and empowerment of Mayan culture; and (3) because its organizational structure combines receiving face-to-face instruction on weekends in the urban campus of San Juan de Chamelco-Cobán, while during the week, students carry out their personal, professional and educational activities in rural areas. Thus, a double dimension has been addressed through this international cooperation project, which has the complex task of training professionals who will work with children in rural areas but who will be trained in San Juan de Chamelco-Cobán, an urban area, the commercial and economic hub of the region, On the one hand, as will be developed further in this article, the selection and initial psycho-pedagogical-curricular training, attention to cultural, gender, and sociological diversity, of university teachers who, in the future, will be entrusted with the implementation and development of a university curriculum in teacher training aimed at and from the inclusion of children from Mayan rural communities. On the other hand, while considering the center’s organizational structure, establishing the fundamental psycho-pedagogical and organizational principles with an inclusive curricular plan will allow the training of teachers whose actions will be carried out in rural Mayan environments. As a starting hypothesis, we consider that in order to provide quality, responsible and inclusive education to children from rural Mayan environments, and beyond the traditionally technical contents that support the training curriculum legislated by the Guatemalan government, it is necessary to approach this reality by linking vitally constructed knowledge and technical contents, so that they can be formulated and reformulated in a relevant way and thus generate powerful knowledge. Thus, there arises a necessity to equip a team of professionals, prospective university teachers, who are sensitive to Mayan needs and attention to diversity, with a deep and relevant knowledge of psycho-pedagogical and curricular aspects, and with a sociological contextual knowledge of the needs of the post-modern, neoliberal and digital world. To this end, our methodology encompasses three levels: (a) the selection of a group of professionals to be trained; (b) contextual analysis of the training needs of the selected group of professionals, thereby facilitating the adaption of the training program to their individual needs and circumstances; and (c) semi-structured and in-depth interviews with seven female and nine male leaders of Mayan communities. These leaders were selected using a non-probabilistic intentional sampling method, which was collaboratively determined with the ITMES team. During these interactions, we extensively explored their perspectives on Mayan identity, as well as their perceptions of the educational system and its impact on the formation of their identity as a person and as Mayans. Through the integration of these three components, we have obtained invaluable insights into (a) the evolving training needs of the instructional team and (b) the socio-educational pressures experienced by Mayan women, and the significance of “Mayan being” as an aspect of identity. This emergent data has informed the development of a comprehensive psycho-pedagogical, curricular and sociological training plan that underpins the content of this article. Thus, for the selection of the training team, the following aspects were considered: knowledge of Mayan culture and experience in rural Mayan contexts and relationship with the educational-school world. The selection resulted in a total of 29 candidates, 18 women and 11 men, with whom the training was carried out. Regarding the initial training plan for university teachers, and after the contextual analysis, we consider it necessary to correlate three dimensions: (1) the psycho-pedagogical nature of the technical dimension. In this sense, the plan has addressed aspects related to the conceptualization of teaching, and of learning and the development of the fundamental aspects of the curriculum; (2) the idiosyncratic dimension of rural Mayan communities, beyond being a transversal axis, has also been incorporated into the plan. We incorporated analyses related to gender, in general, and gender in schools, making a triangulation with the emerging knowledge from the interviews and the conceptualization of inclusion and Mayan identity as the backbone of a quality education; and (3) the post-modern sociological dimension of today’s societies. Finally, a flexible and emerging training plan of the Mayan idiosyncrasy has been designed that allows its applicability in other similar sociological contexts, adapting the plan to the individual training needs of each context.